Approaches to Understanding Multisensory Dysfunction in Autism Spectrum Disorder. Issue 9 (1st September 2020) - Siemann, Justin K.; Veenstra‐VanderWeele, Jeremy; Wallace, Mark T.
Abstract : Abnormal sensory responses are a DSM‐5 symptom of autism spectrum disorder (ASD), and research findings demonstrate altered sensory processing in ASD. Beyond difficulties with processing information within single sensory domains, including both hypersensitivity and hyposensitivity, difficulties in multisensory processing are becoming a core issue of focus in ASD. These difficulties may be targeted by treatment approaches such as "sensory integration, " which is frequently applied in autism treatment but not yet based on clear evidence. Recently, psychophysical data have emerged to demonstrate multisensory deficits in some children with ASD. Unlike deficits in social communication, which are best understood in humans, sensory and multisensory changes offer a tractable marker of circuit dysfunction that is more easily translated into animal model systems to probe the underlying neurobiological mechanisms. Paralleling experimental paradigms that were previously applied in humans and larger mammals, we and others have demonstrated that multisensory function can also be examined behaviorally in rodents. Here, we review the sensory and multisensory difficulties commonly found in ASD, examining laboratory findings that relate these findings across species. Next, we discuss the known neurobiology of multisensory integration, drawing largely on experimental work in larger mammals, and extensions of these paradigms into rodents. Finally, we describe emerging investigations into multisensory processing in genetic mouse models related to autism risk. By detailing findings from humans to mice, we highlight the advantage of multisensory paradigms that can be easily translated across species, as well as the potential for rodent experimental systems to reveal opportunities for novel treatments. Lay Summary: Sensory and multisensory deficits are commonly found in ASD and may result in cascading effects that impact social communication. By using similar experiments to those in humans, we discuss how studies in animal models may allow an understanding of the brain mechanisms that underlie difficulties in multisensory integration, with the ultimate goal of developing new treatments. Autism Res 2020, 13: 1430–1449 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc.